Comparison of lactation diets containing various protein sources on sow and litter performance - Steven S Dritz; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 188 lactating sows was used in Exp. 1 to determine the influence of a complex lactation diet containing oats, linseed meal, and alfalfa meal compared with a corn-soybean meal diet on sow and litter performance. No differences in sow and litter performance were observed. Therefore, a simple corn-soybean meal diet was adequate 10 maximize sow productivity. Average daily feed intake (ADFI) of sows by parity was also examined in Exp. 1. The ADFI of parity 1 sows was considerably lower than that of parity 3 sows, but litter weaning weights were similar. Thus, lactation diet formulation should account for the differences in feed intake by parity and be formulated on ADFI (average daily feed intake) and level of production. A total of 198 lactating sows was used in Exp. 2 to determine the influence of substituting 3 lb/ton of L-lysine HCl and corn for soybean meal in the lactation diet. No differences in sow and litter performances were observed. However, ADFI was excellent for both treatments, resulting in average daily lysine intakes of 67.6 and 69.7 g per day. This is approximately 14 g in excess of the reported requirement for this level of production. Thus, further research is needed to assess the use of L-lysine HCI in lactation diets.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Sows; Protein; Lysine